Upaya Peningkatan Kemampuan Literasi dan Numerasi Siswa SDN 1 Sepanjang Melalui Program Agroschooling - Sukma, Fena Dheta; Sari, Dian Permata; Nirvana, Atnic Satya; Auzai, Ahmad Fani Al; Musthofa, Najichul Fikri; Alauzai, Ahmad Fani Al (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2024)
The improvement of literacy and numeracy skills is a focus of the Indonesian Ministry of Education and Culture (Kemdikbud RI), given the low proficiency of Indonesian students in these areas. The agroschooling program at SDN 1 Sepanjang aims to enhance the literacy and numeracy skills of students through farming activities. The implementation method of this program involves socialization, training, and field practice over a period of three months. Socialization aims to correct understanding of literacy and numeracy, as well as motivate participants to engage in the program. Training provides basic knowledge of plant care, while field practice enables students to apply this knowledge in real farming activities. As a result, students show high enthusiasm and improvement in literacy and numeracy skills through contextual and relevant activities. They learn to select seeds, care for plants, calculate water and fertilizer requirements, and produce progress reports on plant growth. This approach not only teaches academic skills but also instills values of responsibility, cooperation, and environmental stewardship